Pendidikan Karakter di Era Millenial - Siregar, Mustamar Iqbal (Program Studi Pendidikan Agama Islam, 2022)
The discourse on character education is never dry, because until now, Indonesia is still orienting its education towards building national character. But this paper is a little different. Here, the character education model is more flexibly formulated to respond to the reality of the millennial era. Because the presence of the millennial era is a consequence of globalization, it is feared that many parties will weaken the nation's morality and personality. So that with a more flexible formula, it is expected that the millennial generation will be more comfortable following the learning process, without having to lose their ideal character as a generation that is critical, creative, and cultured. With methodological creations this paper tries to offer a model of character education that further suppresses the media-based learning process on four things: scientific honesty, tabayyun method (cross check), encouraging creativity, and building humanist interactions. An educational idea for the millennial generation, which requires the running of an information technology-based education process while being oriented towards character building